2009
DOI: 10.1080/10926750902978865
|View full text |Cite
|
Sign up to set email alerts
|

Reunions of Adoptees Who Have Met Both Birth Parents: Post-Reunion Relationships and Factors that Facilitate and Hinder the Reunion Process

Abstract: Eighteen adoptees who had met both their birth mothers and birth fathers were surveyed in order to determine (a) the types of post-reunion relationships they developed with each birth parent and (b) the factors that facilitated or hindered their reunions. While adoptees were more likely to develop a personal rather than non-personal relationship with birth mothers, relationships with birth fathers were more evenly divided between personal and non-personal relationships. Thematic analysis revealed some similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Using Galvin's (2006) conceptual reunion and the relational meanings of these messages. In addition, this study expands interest to all members of the birth family, when most previous research examined only birth mothers (e.g., March, 1995) or birth parents (e.g., Passmore & Feeney, 2009). …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Using Galvin's (2006) conceptual reunion and the relational meanings of these messages. In addition, this study expands interest to all members of the birth family, when most previous research examined only birth mothers (e.g., March, 1995) or birth parents (e.g., Passmore & Feeney, 2009). …”
mentioning
confidence: 97%
“…Passmore and Feeney (2009) pointed out that further research needs to be conducted to explore the reunions of international, transracial adoptees. In addition, no studies have approached the topic from a communication perspective, which draws attention to the messages that are exchanged during these interactions and the meanings of these messages to involved participants.…”
mentioning
confidence: 98%
“…On close examination of the dynamics of long-term adoption reunions, it has been found that displacement of the adoptive family by the birth family is extremely rare, and that what seems to be emerging are horizontal kinship networks whereby adoptive and birth families co-exist, to a greater or lesser extent for all parties. Although research has concentrated on the adopted person-birth mother dyad (Howe and Feast 2003), in reunions that continue down through the years, the role of siblings, birth grandparents, spouses, and the children of both parties has been neglected (Passmore and Feeney 2009). This research has uncovered that these groupings may play an instrumental part in the development and maintenance of kinship ties.…”
Section: Discussionmentioning
confidence: 99%
“…As can be expected in a relatively new body of knowledge, certain areas and concerns have dominated, with consequent gaps in our understanding. The experiences of adopted people have traditionally made up most of the literature (Baden and Wiley 2007), followed by those of birth mothers (Evan Donaldson Institute 2006), adoptive mothers (Feast et al 2011), and then, far back in the field, birth fathers (Passmore and Feeney 2009), adoptive fathers (Feast et al 2011), and other birth relatives such as siblings (O'Neill et al 2018). Other gaps include perspectives from within sets of reunions, e.g., the experiences of both the birth mother and the adopted person (March 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Research on post-adoption contact has predominantly focused on adopted peoples' reunion and postreunion experiences with their birth mothers (March 1997;Affleck & Steed 2001), with both birth parents (Passmore & Feeney 2009) or with birth relatives in general (Howe & Feast 2000Triseliotis et al 2005). There have also been some studies that focus on the experiences of other parties to the reunion, namely, birth mothers, (Kelly 2005;Henney et al 2007), birth fathers, (Clapton 2003) and adoptive parents (Petta & Steed 2005;Feast et al 2011).…”
Section: Introductionmentioning
confidence: 99%